Penguatan Peraturan Perundang-Undangan Di Indonesia Melalui Teori Legal Maxim - yadi, safriadi safri (Jurnal Legislasi Indonesia, 2025)
AbstractLegislation needs to be strengthened and updated in order to always be in line with current conditions developing in society. One instrument to strengthen it is through the application of legal maxim theory. This research uses a philosophical and juridical approach, with literature study and content analysis. The conclusion is that the drafting of legislative regulations, both within the scope of amendments and formulating new regulations, is based on and based on the principle of legal maxim (rules of jurisprudence). The existence of legal maxims (rules of jurisprudence) is to strengthen laws and regulations through philosophical aspects. Legislative drafters' mastery of legal maxims is absolutely necessary to strengthen the resulting legal products.Key words: Legal Maxim, Legislation AbstrakPeraturan perundang-undangan perlu dilakukan penguatan dan pembaharuan guna senantiasa sesuai dengan kondisi kekinian yang berkembang dalam masyarakat. Salah satu instrument untuk menguatkannay adalah melalui penerapan teori legal maxim. Penelitian ini menggunakan pendekatan filosofis dan yuridis, dengan studi pustaka dan analisis conten. Kesimpulannya bahwa perancangan peraturan perundang-undangan baik dalam ruang lingkup amandemen maupun merumuskan peraturan yang baru didasari dan dilandasi atas asas legal maxim (kaidah fikih). Keberadaan legal maxim (kaidah fikih) ini guna menguatkan peraturan perundang-undangan lewat sisi aspek filosofis. Penguasan para perancang perundang-undangan terhadap legal maxim mutlak diperlukan guna penguatan dari produk Undang-undang yang dihasilkan.Key word: Legal Maxim, Peraturan perundang-undangan